Skin sodium measured with ²³Na MRI at 7.0 T - Linz, Peter; Santoro, Davide; Renz, Wolfgang; Rieger, Jan; Ruehle, Anjuli; Ruff, Jan; Deimling, Michael; Rakova, Natalia; Muller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Niendorf, Thoralf (NMR in Biomedicine, 2015)
Skin sodium (Na(+) ) storage, as a physiologically important regulatory mechanism for blood pressure, volume regulation and, indeed, survival, has recently been rediscovered. This has prompted the development of MRI methods to assess Na(+) storage in humans ((23) Na MRI) at 3.0 T. This work examines the feasibility of high in-plane spatial resolution (23) Na MRI in skin at 7.0 T. A two-channel transceiver radiofrequency (RF) coil array tailored for skin MRI at 7.0 T (f = 78.5 MHz) is proposed. Specific absorption rate (SAR) simulations and a thorough assessment of RF power deposition were performed to meet the safety requirements. Human skin was examined in an in vivo feasibility study using two-dimensional gradient echo imaging. Normal male adult volunteers (n = 17; mean ± standard deviation, 46 ± 18 years; range, 20-79 years) were investigated. Transverse slices of the calf were imaged with (23) Na MRI using a high in-plane resolution of 0.9 × 0.9 mm(2) . Skin Na(+) content was determined using external agarose standards covering a physiological range of Na(+) concentrations. To assess the intra-subject reproducibility, each volunteer was examined three to five times with each session including a 5-min walk and repositioning/preparation of the subject. The age dependence of skin Na(+) content was investigated. The (23) Na RF coil provides improved sensitivity within a range of 1 cm from its surface versus a volume RF coil which facilitates high in-plane spatial resolution imaging of human skin. Intra-subject variability of human skin Na(+) content in the volunteer population was <10.3%. An age-dependent increase in skin Na(+) content was observed (r = 0.78). The assignment of Na(+) stores with (23) Na MRI techniques could be improved at 7.0 T compared with current 3.0 T technology. The benefits of such improvements may have the potential to aid basic research and clinical applications designed to unlock questions regarding the Na(+) balance and Na(+) storage function of skin.
EVALuna2:3754